Problemy funkcjonowania gospodarki opartej na wiedzy w Polsce w warunkach integracji w ramach Unii Europejskiej - Puślecki, Zdzisław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Higher education can be used for accelerating the economic development and for building the new knowledge driven economy in Poland too. Financial aid coming from different programme of financial support, such as the structural funds, for example, may be helpful, to a significant degree, in achieving this goal. At the same time, the financial means of that type facilitate a faster adaptation of the Polish higher education to the Union standards. And this becomes particularly important in the situation of Poland's membership in the European Union. As a result, the ties between higher education, scientific research and production processes, that is, the ties characteristic for knowledge-driven society, will help to reduce unemployment. There is also the need for steady modernization of teaching curricula in existing university specializations. This should be complemented by a broad international co-operation, especially with the best scientific and academic centres. A significant role, in this respect, in less developed countries, also in Poland, is played by the educational processes on the higher level, including the new forms of teaching and learning, such as self-teaching or remote teaching. This is so, because the accelerated adaptation to changing requirements of the job market and to technological transformations, and consequently, the growing significance of a knowledge-driven economy, becomes more and more important. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 265-274